Gerakan Masyarakat Kendeng, Rembang untuk Keadilan dan Penegakan Hak Asasi Manusia - Rizky Agus Harnanto; Atika Ishmatul Ummah; Elsya Rekavianti; Ayu Ratnasari (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2018)
The case of injustices and human rights violations in Kendeng, Rembang Regency become a national issue that has led to the emergence of the social movement to defend the rights of people. LBH Semarang is among CSOs that actively engage in the movement. This research is qualitative and descriptive using LBH Semarang as a case study. By applying observation, interviews and document study, this research found that LBH Semarang Plays important role in organizing the movement to reject the establishment of cement industry in Kendeng.